Stroke survivors’ health literacy is not associated with caregiver burden: a cross-sectional study - Andrea Hess Engström; Sebastian Lindblom; Maria Flink; Susanna Söderberg; Lena von Koch; Charlotte Ytterberg (Scientific Reports)
Abstract Caregivers to stroke survivors often experience a multifaceted strain defined as caregiver burden. Low health literacy among caregivers may contribute to increased caregiver burden but there is limited research specifically examining the association between stroke survivors’ health literacy and caregiver burden. Therefore, the aim here is to explore if there is an association between stroke survivors’ health literacy and caregiver burden one year after stroke. Participants were 50 caregivers and 50 stroke survivors who were followed up in a longitudinal study on care transitions after stroke. Data were collected one year after the stroke survivors’ discharge from hospital and analysed using ordinal logistic regression. Most of the caregivers, median age 71 years, reported being satisfied with their lives (85%) and a low caregiver burden (74%). Stroke survivors’ health literacy was not associated with caregiver burden. However, lower needs of assistance in daily activities, lower levels of depression, higher levels of participation and increased age in stroke survivors were associated with lower caregiver burden. In conclusion, stroke survivors’ health literacy was not associated with caregiver burden one year after stroke. Future studies with larger samples, focusing on populations with lower functioning after stroke and higher caregiver burden, are recommended.